6S RNA in Rhodobacter sphaeroides: 6S RNA and pRNA transcript levels peak in late exponential phase and gene deletion causes a high salt stress phenotype. Issue 11 (2nd November 2017) - Elkina, Daria; Weber, Lennart; Lechner, Marcus; Burenina, Olga; Weisert, Andrea; Kubareva, Elena; Hartmann, Roland K.; Klug, Gabriele
ABSTRACT: The function of 6S RNA, a global regulator of transcription, was studied in the photosynthetic α-proteobacterium Rhodobacter sphaeroides . The cellular levels of R. sphaeroides 6S RNA peak toward the transition to stationary phase and strongly decrease during extended stationary phase. The synthesis of so-called product RNA transcripts (mainly 12–16-mers) on 6S RNA as template by RNA polymerase was found to be highest in late exponential phase. Product RNA ≥ 13-mers are expected to trigger the dissociation of 6S RNA:RNA polymerase complexes. A 6S RNA deletion in R. sphaeroides had no impact on growth under various metabolic and oxidative stress conditions (with the possible exception of tert-butyl hydroperoxide stress). However, the 6S RNA knockout resulted in a robust growth defect under high salt stress (0.25 M NaCl). Remarkably, the sspA gene encoding the putative salt stress-induced membrane protein SspA and located immediately downstream of the 6S RNA ( ssrS ) gene on the antisense strand was expressed at elevated levels in the Δ ssrS strain when grown in the presence of 250 mM NaCl.